Sustained impacts of the COVID-19 pandemic on medical student learning and well-being in rural Australia: findings from a repeated national multicentre survey - Srinivas Kondalsamy-Chennakesavan; Priya Martin; Matthew R McGrail; Penny Allen; Remo Ostini; Lara Fuller; Jordan Fox; Jessica Beattie; Zelda Doyle (BMJ Open)
Objective The impact of COVID-19 on medical students has predominantly been assessed by one-off survey studies at the pandemic onset. This national study investigated the sustained impacts of the COVID-19 pandemic on medical students’ rural clinical placement learning and well-being.Design Repeated cross-sectional survey design.Setting Annual Federation of Rural Australian Medical Educators (FRAME) survey across 2020 to 2022.Participants Medical students completing an extended (mostly 12 months) rural placement.Outcome measure A mixed-methods survey with closed-ended and open-ended question. Quantitative data were analysed using χ2 and Kruskal-Wallis tests. Qualitative responses were analysed through content analysis.Results Quantitative findings: in 2022 (43%), respondents were more likely to interact with COVID-19 patients in a clinical capacity compared with 2020 (26%) and 2021 (23%; p<0.001). Respondents were more likely to be concerned about missed clinical learning in 2020 (58%) than in 2021 (40%) and 2022 (44%; p<0.001). Respondents in 2020 (41%) and 2022 (39%) were more likely to feel that their performance on assessments was affected by COVID-19 compared with 2021 respondents (28%; p<0.001). Respondents in 2022 (38%) and 2021 (31%) were more likely to report being exposed to an increased breadth of cases than 2020 respondents (13%; p<0.001) and also reported more exposure to community-based placements (2022: 38%, 2021: 31%, 2020: 19%; p<0.001).Qualitative findings: three categories were developed from the data—mental health and well-being impacts, learning preferences at play, and concerns about flow-on effects.Conclusions While the pandemic has now become the ‘new normal’, the mental well-being and learning concerns raised by students in rural Australia, and their concerns about sustained impacts into their internship cannot be ignored. Healthcare organisations need to ensure that when impacted students enter the workforce the practice context is supportive, with mechanisms such as effective clinical supervision in place.